Assessment of the Influence of Weather Factors on the Quantitative Indicators of Sweet Cherry Fruits by Ridge Regression - Ivanova, Iryna; Serdyuk, Maryna; Malkina, Vira; Tymoshchuk, Tetiana; Shkinder-Barmina, Anna; Іванова, Ірина Євгенівна; Сердюк, Марина Єгорівна; Малкіна, Віра Михайлівна; Тимощук, Тетяна Миколаївна; Шкіндер-Барміна, Анна Миколаївна (Zhytomyr : Polissia National University, 2022)
EN: Sweet cherries are a favourite stone crop among consumers of fruit products. At present, the demand for sweet cherries is growing, which encourages the expansion of the varietal range of crops with different ripening periods. The purpose of this study was to develop a mathematical model for predicting the formation of fruit and sweet cherry pyrene mass depending on weather factors and varietal characteristics. The study was conducted during 2008-2019 in the conditions of the Southern Steppe zone of Ukraine on 33 varieties of sweet cherries of early, medium, and late ripening periods. The average mass of the sweet cherry fruit over the years of research was 8.41 g, and the average mass of the pyrene was 0.56 g. Late-ripening sweet cherry varieties had the best fruit mass (7.27-12.18 g). According to the maximum average mass of the fruit, the varieties Kazka, Dilema, and Kosmichna were distinguished. Rubinova Rannia, Pervistok, Melitopol black and Krupnoplidna varieties had the lowest pyrene mass in sweet cherry fruits. In the group of early ripening, the best ratio of pyrene to fruit pulp was found in the Kazka variety, in medium-ripening varieties – Cordia, Perviystok, and Orion, in late-ripening varieties – Udivitelna, Krupnoplidna, and Prazdnichna. The smallest variability in sweet cherry fruit mass in the group of early-ripening varieties was detected in Sweet Erlise, in mid-ripening – Temp, and in late-ripening – Regina, while in pyrene mass – Rubinova Rannia, Vynka and Regina, respectively. Weather conditions had a dominant influence on the formation of fruit mass for all sweet cherry varieties under study, and varietal characteristics had a dominant effect on pyrene mass. The maximum influence on the formation of sweet cherry fruit mass of early varieties was provided by the indicator – the number of days with precipitation in May exceeding 1 mm, and for medium and late ripening varieties – the average monthly amount of precipitation in June. Decisive importance for the formation of pyrene mass in sweet cherry fruits of early ripening varieties was the average monthly amount of precipitation in May, in the middle ripening period – the average monthly amount of precipitation in June, in the late ripening period – the number of days with precipitation exceeding 1 mm in May. UA: Черешня є улюбленою кісточковою культурою у споживачів плодової продукції. Наразі попит на черешню зростає, що спонукає розширити сортовий асортимент культури з різними строками достигання. Метою досліджень було розробити математичну модель для прогнозу формування маси плоду і кісточки черешні залежно від погодних факторів і сортових особливостей. Дослідження проводили протягом 2008–2019 рр. в умовах Південної Степової зони України на 33 сортах черешні раннього, середнього і пізнього строків достигання. Середня маса плоду черешні за роки досліджень становить 8,41 г, а середня маса кісточки – 0,56 г. Сорти черешні пізнього строку достигання мали оптимальну масу плодів (7,27–12,18 г). За максимальною середньою масою плоду виділено сорти Казка, Ділема і Космічна. Найменшу масу кісточки у плодах черешні мали сорти Рубінова рання, Первисток, Мелітопольска чорна і Крупноплідна. У групі раннього строку достигання оптимальне співвідношення кісточки до м’якоті плодів визначено у сорту Казка, у середньостиглих – Кордія, Первісток і Оріон, у пізньостиглих – Удівітєльна, Крупноплідна і Празднічна. Найменшу варіативність за масою плодів черешні у групі ранньостиглих сортів виділено Sweet Erlise, середньостиглих – Темп і пізньостиглих – Регіна, а за масою кісточки – Рубінова Рання, Винка і Регіна відповідно. На формування маси плоду домінуючий вплив для усіх досліджуваних сортів черешні мали погодні умови, а маси кісточки – сортові особливості. Максимальний вплив на формування маси плоду черешні ранніх сортів забезпечив показник – кількість днів з опадами у травні більше 1 мм, а середньо- і пізньостиглих сортів – середньомісячна сума опадів в червні. Вирішальне значення на формування маси кісточки у плодах черешні сортів раннього строку достигання має середньомісячна сума опадів у травні, середнього строку достигання – середньомісячна сума опадів в червні, пізнього строку достигання – кількість днів з опадами в травні більше 1 мм.
Оцінка впливу погодних факторів на кількісні показники плодів черешні методом Ridge-регресії
Keywords: pyrene mass; fruit mass; the ratio of pyrene to fruit pulp; variation of indicators;climatic conditions; regression model; маса кісточки; маса плоду; співвідношення кісточки до м’якоті плоду; варіація показників; кліматичні умови; регресійна модель